Gambaran Motivasi Membaca Anak Sekolah Dasar di Ruang Publik Terpadu Ramah Anak X, Jakarta Barat - Naibaho, Yunita Olip; Ompusunggu, Carine; Napitupulu, Michele Tesalonika Nauli; Wati, Linda (Prodi Psikologi- Fakultas Psikologi & Humaniora - Universitas Teknologi Sumbawa, 2025)
This study aims to describe the reading motivation of elementary school-aged children who are active in RPTRA X, West Jakarta. The method used is descriptive quantitative with 35 participants, using five dimensions of Motivations for Reading Questionnaire as the instrument. Mean scores, standard deviations, and group comparisons were analyzed using SPSS 26. The results show that the Reading Curiosity dimension had the highest score, indicating curiosity as the main driver of reading. Conversely, Reading Work Avoidance had the lowest score, indicating a negative perception of reading activities. A significant difference was found in the Social Reasons for Reading dimension based on gender, with girls being more socially motivated to read. These findings highlight the need for engaging literacy approaches to reduce reading avoidance. The study underscores the importance of developing adaptive, interactive, and interest-based community literacy programs, enabling RPTRA to serve as an effective and sustainable literacy space.